Long-term anticoagulant therapy in the aspect of secondary prevention of recurrent pulmonary embolism - E. A. Shmidt; T. Yu. Penskaya; O. V. Gruzdeva; S. A. Berns; V. N. Karetnikova; O. L. Barbarash (Кардиоваскулярная терапия и профилактика, 2024)
Aim. To determine differences in laboratory coagulation parameters using routine and integral monitoring methods in patients depending on anticoagulant therapy >12 months after pulmonary embolism (PE) with a high recurrence risk.Material and methods. The study included 72 patients who, according to indications, received long-term anticoagulant therapy >12 months due to a high risk of recurrent thromboembolism. During the follow-up period (15-20 months from the first pulmonary embolism episode), the plasma coagulation parameters were studied using a conventional panel and D-dimer assessment, as well as a thrombin generation test and thrombodynamics. Patients adherent to prolonged anticoagulation were included in group 1. During the collection period, 8 patients independently stopped taking anticoagulants, despite the high risk of recurrent pulmonary embolism (group 2).Results. There were no significant differences in coagulation parameters and D-dimer levels between the studied groups of patients. In the group of patients continuing to take anticoagulants, there was an increase in clot growth delay parameters in comparison with patients of group 2 according to the thrombodynamics results (p=0,046) and the thrombin generation test in platelet-poor plasma in comparison with reference values (p=0,001).Conclusion. Long-term anticoagulant therapy effectively prevents recurrent venous thromboembolism. In patients after primary pulmonary embolism who refuse anticoagulation, the clot growth delay values are shortened, which indicates an increased risk of recurrent venous thromboembolism. The most stable plasma coagulation parameters are observed in patients taking direct oral anticoagulants.